2011
DOI: 10.1007/s10620-011-1819-3
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Arterial Stiffness and Nonalcoholic Fatty Liver Disease

Abstract: Arterial stiffness was independently associated with the prevalence risk for NAFLD regardless of classical CVD risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 31 publications
0
51
0
5
Order By: Relevance
“…Recent studies have shown that age and body mass index (BMI) are independent risk factors for the progression of arterial stiffness (Choi et al, 2013;Pal and Radavelli-Bagatini, 2013). Two Korean studies reported an independent association between baPWV and NAFLD in general subjects including the elderly (Kim et al, 2012;Lee et al, 2012). Considering that the incidence of NAFLD decreases with age (Lonardo et al, 2006) and increases with BMI (Vernon et al, 2011), general subjects may not be representative of the young and middle-aged population which are non-obese, non-hypertensive, and non-diabetic, and thus may not be useful for suggesting the direct association between NAFLD and arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that age and body mass index (BMI) are independent risk factors for the progression of arterial stiffness (Choi et al, 2013;Pal and Radavelli-Bagatini, 2013). Two Korean studies reported an independent association between baPWV and NAFLD in general subjects including the elderly (Kim et al, 2012;Lee et al, 2012). Considering that the incidence of NAFLD decreases with age (Lonardo et al, 2006) and increases with BMI (Vernon et al, 2011), general subjects may not be representative of the young and middle-aged population which are non-obese, non-hypertensive, and non-diabetic, and thus may not be useful for suggesting the direct association between NAFLD and arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Given the different methods used to diagnose NAFLD and different populations chosen to perform studies, results are inconsistent. [5][6][7][8][9][10][11][12][13] In some relatively small samples from the community population, ultrasonographically diagnosed NAFLD has been found to be independently associated with carotid atherosclerosis and arterial stiffness. 6,7 Biopsy-proven NAFLD patients had remarkably greater carotid intimamedia thickness (CIMT) compared with that of age-, sex-, and body mass index (BMI)-matched healthy subjects in a case-control study.…”
mentioning
confidence: 99%
“…Blood viscosity was higher in patients with NAFLD and was independently associated with AWS, even after adjusting for other risk factors. NA-FLD connection with AWS increase was presented in the study of Lee et al (2012). An independent association between PVPW and NAFLD, independently of other cardiovascular risk factors, was found with the help of multivariate regression analysis [116].…”
Section: Arterial Stiffnessmentioning
confidence: 96%
“…In addition, PVPW does not increase in the early stages of atherosclerosis and increases with the development of atherosclerotic plaques, mainly due to calcification of the arterial wall [31]. The increase in AWS in NAFLD was found [115][116][117]. However, the pathogenetic mechanisms of AWS formation in patients with NAFLD are completely unclear.…”
Section: Arterial Stiffnessmentioning
confidence: 99%